Peripheral Interaction of Resolvin D1 and E1 with Opioid Receptor Antagonists for Antinociception in Inflammatory Pain in Rats - Oehler, Beatrice; Mohammadi, Milad; Perpina Viciano, Cristina; Hackel, Dagmar; Hoffmann, Carsten; Brack, Alexander; Rittner, Heike L. (Frontiers in Molecular Neuroscience, 2017)
Antinociceptive pathways are activated in the periphery in inflammatory pain, for instance resolvins and opioid peptides. Resolvins are biosynthesized from omega-3 polyunsaturated fatty acids such as eicosapentaenoic acid and docosahexaenoic acid. Resolvin D1 (RvD1) and resolvin E1 (RvE1) initiate the resolution of inflammation and control of hypersensitivity via induction of anti-inflammatory signaling cascades. RvD1 binds to lipoxin A4/annexin-A1 receptor/formyl-peptide receptor 2 (ALX/FPR2), RvE1 to chemerin receptor 23 (ChemR23). Antinociception of RvD1 is mediated by interaction with transient receptor potential channels ankyrin 1 (TRPA1). Endogenous opioid peptides are synthesized and released from leukocytes in the tissue and bind to opioid receptors on nociceptor terminals. Here, we further explored peripheral mechanisms of RvD1 and chemerin (Chem), the ligand of ChemR23, in complete Freund’s adjuvant (CFA)-induced hindpaw inflammation in male Wistar rats. RvD1 and Chem ameliorated CFA-induced hypersensitivity in early and late inflammatory phases. This was prevented by peripheral blockade of the µ-opioid peptide receptor (MOR) using low dose local naloxone or by local injection of anti-β-endorphin and anti-met-enkephalin antibodies. Naloxone also hindered antinociception by the TRPA1 inhibitor HC-030031. RvD1 did not simulate the release of β-endorphin from macrophages and neutrophils, nor did RvD1 itself activate G-proteins coupled MOR or initiate β-arrestin recruitment to the membrane. TRPA1 blockade by HC-030031 in inflammation in vivo as well as inhibition of the TRPA1-mediated calcium influx in dorsal root ganglia neurons in vitro was hampered by naloxone. Peripheral application of naloxone alone in vivo already lowered mechanical nociceptive thresholds. Therefore, either a perturbation of the balance of endogenous pro- and antinociceptive mechanisms in early and late inflammation, or an interaction of TRPA1 and opioid receptors weaken the antinociceptive potency of RvD1 and TRPA1 blockers. Thus, we hypothesize a dysequillibrium in the pro- and antinociceptive machinery in inflammatory pain.